GIỚI THIỆU KHÁI QUÁT VỀ PHẦN MỀM TRA CỨU KHOÁNG VẬT MMINERALS 2.01 - Trường, Nguyễn Ngọc; Minh, Đàm Quang; Dương, Nguyễn Thùy; Thảo, Hoàng Thị Minh; Thúy, Trần Thị Thanh; Nhàn, Trần Thị Thanh; Quy, Trần Đăng (Vietnam Journal of Earth Sciences, 2017)
Mineral indentifiation from mineral assocciations and application of mineral are problems that havebeen interested in by the researchers from   differentfield of studies, especially in geology. Computerscience is now rooted on many fields of studiesand gained great successes. However, the field of mineralogy in Vietnam has not got any useful software to search minerals yet. With our tireless efforts for two years, we had completed the MMineral 2.01.